2022
DOI: 10.1007/s10055-022-00703-w
|View full text |Cite
|
Sign up to set email alerts
|

Do individual constraints induce flexibility of visual field dependence following a virtual immersion? Effects of perceptive style and cybersickness

Abstract: Accurately perceiving the gravitational direction is key to successful interaction in our terrestrial environment. In this context field dependence (FD), the importance given to static and/or dynamic visual cues, has largely been discussed. Although first considered a trait, several studies suggest FD be flexible in response to postural or visual contexts and to poor virtual reality user experience. The aim of this study was therefore to determine the influence of a disruptive virtual immersion on the level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Other individual characteristics could influence cybersickness and postural changes, such as field dependency [57], the cognitive influence of movement belief [58], or the brain's ability to reweigh sensory information, especially vestibular sensitivity. Subjective vection sensitivity [53] can be influenced by aging and could influence adaptation and habituation capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Other individual characteristics could influence cybersickness and postural changes, such as field dependency [57], the cognitive influence of movement belief [58], or the brain's ability to reweigh sensory information, especially vestibular sensitivity. Subjective vection sensitivity [53] can be influenced by aging and could influence adaptation and habituation capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that the MSSQ score does not show a strong correlation with VIMSSQ score in previous paper [26]. Likewise MISSQ score are reported to have a low to moderate correlation with Simulator sickness questionnaire (SSQ) scores in [27], [28], [29], [30].…”
Section: Questionnairesmentioning
confidence: 80%
“…However, the RFT has been used in studies investigating the relationship between visual perception and motion sickness, which is a similar condition to cybersickness. Research has shown that individuals who are more susceptible to motion sickness tend to exhibit greater variability in their visual perception of the vertical, as measured by the RFT [29]. This suggests that an individual's ability to maintain a stable perception of vertical orientation may be related to their susceptibility to motion sickness.…”
Section: Rod and Frame Testmentioning
confidence: 99%
See 1 more Smart Citation
“…This could enable the use of a 'stronger' (i.e., lower transparency) dFOV modification in those that do not utilize peripheral visual cues as much as others. Individual differences in field dependence that have recently been implicated in cybersickness (Fantin et al 2022) could also provide valuable targets when considering an individually tailored dFOV modifier.…”
Section: Discussionmentioning
confidence: 99%